Risk of aortic dissection, congestive heart failure, pneumonia and acute respiratory distress syndrome in patients with clinical vertebral fracture: a nationwide population-based cohort study in Taiwan - Cheng-Li Lin; Feng-You Lee; Wei-Kung Chen; Tse-Yen Yang; Ching-Yuan Lai (BMJ Open)
Objective Studies on the association between clinical vertebral fractures (CVFs) and the subsequent risk of cardiopulmonary diseases, including aortic dissection (AD), congestive heart failure (CHF), pneumonia and acute respiratory distress syndrome (ARDS) are scarce. Therefore, we used the National Health Insurance Research Database to investigate whether patients with CVF have a heightened risk of subsequent AD, CHF, pneumonia and ARDS.Design The National Health Insurance Research Database was used to investigate whether patients with CVFs have an increased risk of subsequent AD, CHF, pneumonia and ARDS.Participants This cohort study comprised patients aged ≥18 years with a diagnosis of CVF and were hospitalised at any point during 2000–2010 (n=1 08 935). Each CVF patient was frequency-matched to a no-CVF hospitalised patients based on age, sex, index year and comorbidities (n=1 08 935). The Cox proportional hazard regressions model was used to estimate the adjusted effect of CVF on AD, CHF, pneumonia and ARDS risk.Results The overall incidence of AD, CHF, pneumonia and ARDS was higher in the CVF group than in the no-CVF group (4.85 vs 3.99, 119.1 vs 89.6, 283.3 vs 183.5 and 9.18 vs 4.18/10 000 person-years, respectively). After adjustment for age, sex, comorbidities and Charlson comorbidity index score, patients with CVF had a 1.23-fold higher risk of AD (95% CI=1.03–1.45), 1.35-fold higher risk of CHF (95% CI=1.30–1.40), 1.57-fold higher risk of pneumonia (95% CI=1.54–1.61) and 2.21-fold higher risk of ARDS (95% CI=1.91–2.57) than did those without CVF. Patients with cervical CVF and SCI were more likely to develop pneumonia and ARDS.Conclusions Our study demonstrates that CVFs are associated with an increased risk of subsequent cardiopulmonary diseases. Future investigations are encouraged to delineate the mechanisms underlying this association.